Effects of outside air temperature on the preparation of antineoplastic drug solutions in biological safety cabinets. (August 2015) - Umemura, Masayuki; Itoh, Akio; Ando, Yuichi; Yamada, Kiyofumi; Wakiya, Yoshifumi; Nabeshima, Toshitaka
Purpose: In Japan, biological safety cabinets are commonly used by medical staff to prepare antineoplastic agents. At the Division of Chemotherapy for Outpatients, Nagoya University Hospital, a class II B2 biological safety cabinet is used. The temperature inside this biological safety cabinet decreases in winter. In this study, we investigated the effect of low outside air temperature on the biological safety cabinet temperature, time required to admix antineoplastic agents, and accuracy of epirubicin weight measurement. Methods: Studies were conducted from 1 January to 31 March 2008 (winter). The outside air temperature near the biological safety cabinet intake nozzle was compared with the biological safety cabinet temperature. The correlation between the outside air temperature and the biological safety cabinet temperature, time for cyclophosphamide and gemcitabine solubilization, and accuracy of epirubicin weight measurement were investigated at low and high biological safety cabinet temperatures. Result: The biological safety cabinet temperature correlated with the outside air temperature of 5–20℃ ( p  < 0.0001). Compared to cyclophosphamide and gemcitabine solubilization in the biological safety cabinet at 25℃, solubilization at 10℃ was significantly delayed ( p  < 0.01 and p  < 0.0001, respectively). Measurement of epirubicin weight by using a syringe lacked accuracy because of epirubicin's high viscosity at low temperatures ( p  < 0.01). Conclusion: These results suggest that the biological safety cabinet temperature decreases when cool winter air is drawn into the biological safety cabinet, affecting the solubilization of antineoplastic agents. We suggest that a decrease in biological safety cabinet temperature may increase the time required to admix antineoplastic agents, thereby increasing the time for which outpatients must wait for chemotherapy.